An introduction to analysis : from number to integral - Mikusinski, Jan.; Mikusinski, Piotr (New York : John Wiley and Sons, 1993)
This book is about: Natural numbers; Real numbers; Functions; Sequences and series; Complements to the theory of limits; ...
Keywords: Mathematical analysis; Mathematical analysis